2011
DOI: 10.1089/jmf.2010.1450
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity and Antioxidative Effects of Purple Sweet Potato Extract in 3T3-L1 AdipocytesIn Vitro

Abstract: The purpose of the current study was to determine the anti-obesity and anti-inflammatory effects of an extract of purple sweet potatoes (PSPs) on 3T3-L1 adipocytes. For this purpose, differentiated 3T3-L1 adipocytes were treated with a PSP extract at concentrations of 1,000, 2,000, and 3,000 μg/mL for 24 hours. Then, we measured the changes in the sizes of the adipocytes, the secretion of leptin, and the mRNA/protein expression of lipogenic, inflammatory, and lipolytic factors after the treatment with the PSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 31 publications
3
27
0
1
Order By: Relevance
“…Using the WT and transgenic sweet potato, the ROS scavenging capacity of anthocyanins was validated in vivo with or without stressful conditions (Figure 7), although a few studies have shown a similar effect using extracted anthocyanins from various sweet potato genotypes [35], [61], [62]. The reduced antioxidant activity in sweet potato lacking anthocyanins also confirmed the protective function of anthocyanins in plants as a conserved mechanism of stress resistance.…”
Section: Discussionmentioning
confidence: 80%
“…Using the WT and transgenic sweet potato, the ROS scavenging capacity of anthocyanins was validated in vivo with or without stressful conditions (Figure 7), although a few studies have shown a similar effect using extracted anthocyanins from various sweet potato genotypes [35], [61], [62]. The reduced antioxidant activity in sweet potato lacking anthocyanins also confirmed the protective function of anthocyanins in plants as a conserved mechanism of stress resistance.…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with other studies, MDI stimulation modulated mRNA levels of genes involved in these processes in differentiated 3T3-L1 cells (Figs. 4B and 4C) [12], [36]. To examine the effect of SG on the progression of lipogenesis and lipolysis, we determined mRNA levels of lipogenic molecules such as LPL, aP2, FAS, FATP1, and HMG-CoA by RT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that purple sweet potato (Ipomoea batatas L.) is an efficient free radical scavenger that can help the antioxidant defense system because of its constituent anthocyanins. [13][14][15] Physiological effects of purple sweet potato include antioxidant, 13,14 antiobesity, 13 antitumor, 14 and anti-inflammation. 15 Purple sweet potato decreases the overproduction of TNF-a in lipopolysaccharide (LPS)-induced acute inflammation.…”
Section: Introductionmentioning
confidence: 99%